Global distribution of the population with disabilities in relation to geographic patterns of human development - Cutillas Orgilés, Ernesto (Documents d'Anàlisi Geogràfica, 2017)
Various scientific approaches have studied the living spaces where existing environmental and social factors hinder the access and participation of people with disabilities. In this regard, the distribution of the population with disabilities broadly parallels the distribution of other social indicators and development worldwide. In this paper, we consider a set of indicators from the World report on disability to identify those that better explain the geographical distribution of years lived with disability (YLD) on a global scale. Despite the limitations of the data sources and the difficulty of establishing cause-effect relationships, the results reveal that the prevalence of disability is not always linked to the aging population in developing countries, while the population with a high YLD increases in regions where levels of human development and the gender inequality index reflect significant social disparities.